The effect of transcranial direct current stimulation: a role for cortical excitation/inhibition balance? - Krause, Beatrix; Márquez-Ruiz, Javier; Cohen Kadosh, Roi (Frontiers in Human Neuroscience, 2013)
Transcranial direct current stimulation (tDCS) is a promising tool for cognitive enhancement and neurorehabilitation in clinical disorders in both cognitive and clinical domains (e.g., chronic pain, tinnitus). Here we suggest the potential role of tDCS in modulating cortical excitation/inhibition (E/I) balance and thereby inducing improvements. We suggest that part of the mechanism of action of tDCS can be explained by non-invasive modulations of the E/I balance.